Therapeutic Application of Bacteriophage PHB02 and Its Putative Depolymerase Against Pasteurella multocida Capsular Type A in Mice - Chen, Yibao; Sun, Erchao; Yang, Lan; Song, Jiaoyang; Wu, Bin (Frontiers in Microbiology, 2018)
Phage PHB02 specifically infects Pasteurella multocida capsular serogroup A strains. In this study, we found that capsule deletion mutants were not lysed by PHB02, suggesting that the capsule of P. multocida serogroup A strains might be the primary receptor. Based on sequence analysis, a gene encoding a phage-associated putative depolymerase was identified. The corresponding recombinant depolymerase demonstrated specific activity against capsular serogroup A strains but did not strip capsule deletion mutants. In vivo experiments showed that PHB02 was retained at detectable levels in the liver, spleen, kidney, lung, and blood at 24 h post-administration in mice. Depolymerase plus serum significantly reduced the number of viable wild-type P. multocida strain HB03 cells (3.5–4.5 log decrease in colony-forming units). Moreover, treatment with phage or purified depolymerase resulted in significantly increased survival of mice infected with P. multocida HB03, and an absence of increase of eosinophils and basophils or other pathological changes compared with the control group. These results show that phage PHB02 and its putative depolymerase represent a novel strategy for controlling P. multocida serogroup A strains.